2011
DOI: 10.5171/2011.598357
|View full text |Cite
|
Sign up to set email alerts
|

Testing Web Services Composition: A Mapping Study

Abstract: E-business systems are known for their frequent changes in business requirements, and traditional software development engineering approaches have difficulties in keeping up with this dynamicity. The use of service oriented architecture in software development has become popular as it provides a solution to frequent changes to business environments in a heterogeneous network. In service oriented architecture, new systems are quickly developed by combining services developed and owned by different organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…There are related SMS investigating the alignment of requirements specification and testing such as presented in [5]. In [52], the authors conducted a survey to examine the use of UML profiles for testing Web services composition.…”
Section: Smss and Slrs Applied To Uml Profilesmentioning
confidence: 99%
“…There are related SMS investigating the alignment of requirements specification and testing such as presented in [5]. In [52], the authors conducted a survey to examine the use of UML profiles for testing Web services composition.…”
Section: Smss and Slrs Applied To Uml Profilesmentioning
confidence: 99%
“…These models and frameworks and tools have additional overhead and are not sufficient on multiple and different platforms while testing web service [34]. It has been observed that for multi dimension platforms, there are essential requirements for web service testing teams to work in this way [35]. In order to incorporate industry level web service testing, a comprehensive resolution [36] should be recommended to get the expected results.…”
Section: Research Methods and Motivationmentioning
confidence: 99%
“…Technique/Method [4], [29], [6], [14], [22], [34], [35], [36], [37], [32], [40], [41], [38] Tool [39], [10], Framework/Model [21], [18], [40], [9], [7], [11] The classification of selected primary study that has SOAP and RESTful web service type support are presented in Fig. 7, which shows a sample illustration of the types of existing web service.…”
Section: Contribution Types Referencesmentioning
confidence: 99%
“…An overview and timeline of different testing approaches for service compositions has recently been given by Rusli et al . . Our approach is also influenced by early works that introduced data flow‐oriented program testing (e.g.…”
Section: Related Workmentioning
confidence: 99%